MICRO-LEAKAGE OF PREHEATED COMPOSITE AS A CEMENTATION MATERIAL IN INDIRECT ADHESIVE RESTORATION (LITERATURE REVIEW) - Mirza Aryanto (Universitas Baiturrahmah, 2022)
Introduction: Composite resin is a material that is often used to perform dental restorations, but it can cause a deficiency called polymerization shrinkage which can be overcome by preheating the composite material. In several studies, there are differences of opinion regarding using preheating techniques at 60oC to overcome polymerization shrinkage. Review: This article intends to analyze the level of microleakage on the restoration of adhesive indirectly as cementing materials with preheated composites. A total of 49 journals from PubMed, NCBI, BMC, Research gate, Z-library, EBSCO, Google Scholar, and other international journal websites were analyzed. Conclusion: The preheating method showed samples with heating of 60oC had statistically lower microleakage at cervical margins. However, preheating resulted in an increase in the contraction voltage of undesirable polymerization.